Viability, growth and toxicity of Alexandrium catenella and Alexandrium minutum (Dinophyceae) following ingestion and gut passage in the oyster Crassostrea gigas - Laabir, Mohamed; Amzil, Zouher; Lassus, Patrick; Masseret, Estelle; Tapilatu, Yosmina; De Vargas, Romain; Grzebyk, Daniel (EDP Sciences, 2007)
Adult oysters Crassostrea gigas were experimentally fed with Alexandrium catenella and Alexandrium minutum which are responsible for recurrent toxic blooms in French coastal waters. C. gigas produced faeces and pseudofaeces containing intact and viable temporary pellicular cysts of these two Paralytic toxin producing species. When incubated in favourable conditions, these pellicular cysts were able to germinate at high rates (between 74 and 94%) and the resulting vegetative cells divided with growth rates close to the non-ingested cells (control). The toxin profile of the vegetative cells originated from the germinated temporary cysts was analyzed by liquid chromatography/ fluorescence detection. Total toxin content of newly germinated cells was lower than that of cultured cells. Besides, cell contents of C2, B1, B2 and dcGTX3 toxins featured some changes. Our results suggest that the increased spreading of toxic dinoflagellates through the transfer of shellfish from contaminated towards pristine coastal areas cannot be ruled out. We also suggest that pellicular cysts and newly germinated cells could represent a potential way for the transfer of paralytic toxins toward the higher trophic levels. Des huîtres creuses adultes Crassostrea gigas ont été alimentées en laboratoire avec Alexandrium catenella et Alexandrium minutum, deux dinoflagellés responsables de la bioaccumulation de toxines paralysantes dans les mollusques cultivés dans les eaux côtières françaises. C. gigas a produit des fèces et des pseudofèces contenant des kystes pelliculaires intacts et viables des deux dinoflagellés testés. Une fois replacés dans des conditions de culture favorables, ces kystes temporaires ont germé dans des proportions élevées (entre 74 et 94 %) et les cellules végétatives résultantes se sont divisées avec des taux de croissance proches de ceux des cellules non ingérées (témoins). Le profil toxinique des cellules végétatives, issues des kystes ayant germé, a été analysé par chromatographie liquide/fluorescence. La quantité ...